(untitled) - Kramer, Stephen P. (New York)
Uses questions about hypothetical situations to introduce the process of thinking according to scientific method.
Keywords: Science, Science,Khoa học,Khoa học; Methodology,Juvenile literature,Methodology,Phương pháp,Tài liệu lứa tuổi vị thành niên,Phương pháp